Análise mecânica e microestrutural da junta soldada de aço lhr355 usado em guindaste de plataforma offshore - Borges, Mateus Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
With the advancement of technology and a steady increase in the world's population, today's society needs ever larger and more sophisticated constructions, thus leading engineers, designers and builders to employ ever more resilient and hard-working materials, having as one of the main objectives a decrease in weight of the final product. These considerations are not applied in the case of fixed structures, but mainly in mobile installations, and in the case of this work in offshore equipment. Taking into consideration the applications, complex materials are made more and more processed, so that it offers satisfactory mechanical characteristics (such as strength and ductility) besides the production in the welding process. The main objective of this work was to carry out a study on how a mechanical property of the material-base and the joint welded by the MIG / MAG process of a LHR355 steel tube used in Offshore Cranes for oil and gas exploration platforms. After a metallography and tests such as microhardness, traction and fatigue, it was possible to conclude that the material meets the requirements necessary to be applied in this segment

Com o avanço da tecnologia e aumento constante da população mundial, a sociedade atual necessita de construções cada vez maiores e mais sofisticadas, isso tem levado os engenheiros, projetistas e construtores a empregar materiais cada vez mais resistentes e trabalhados, tendo como um dos objetivos principais a diminuição de peso do produto final. Essas considerações não se aplicam somente ao caso de estruturas fixas, mas principalmente em estruturas móveis, e no caso deste trabalho nos equipamentos offshore. Levando em consideração essas aplicações, se faz necessário materiais cada vez mais processados, de tal forma que ofereçam características mecânicas satisfatórias (como resistência e ductilidade) além da resistência ao processo de soldagem. O principal objetivo deste trabalho foi realizar um estudo sobre as propriedades mecânicas do material-base e da junta soldada pelo processo MIG/MAG de um tubo de aço LHR355 utilizado em Guindastes Offshore de plataformas de prospecção de petróleo e gás. Após a realização de metalografia e ensaios como microdureza, tração e fadiga, foi possível concluir que o material atende os requisitos necessários para ser aplicado neste segmento
Mechanical and microstructural analysis of welded steel lhr355 used in offshore platform crane
Keywords: Soldagem; Guindastes, etc; Fadiga; Welding